2007
DOI: 10.1520/jai101230
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Repassivation Potential of Alloy 22 Using the Potentiodynamic-Galvanostatic-Potentiostatic Method

Abstract: Traditionally, the susceptibility of Alloy 22 (N06022) to suffer crevice corrosion has been measured using the Cyclic Potentiodynamic Polarization (CPP) technique (ASTM G 61). When the alloy is not very susceptible to crevice corrosion, the values of repassivation potential obtained using the CPP technique are not highly reproducible. To circumvent the large uncertainty in the values of the repassivation potential by the CPP method, the repassivation potential of Alloy 22 may be measured using a slower method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…They found that when the applied torque is too low, the determined E R,CREV tend to be inordinately high, but for a torque higher than 0.98 N·m (0.1 kgf·m) the measurement becomes stable. The same tendency was displayed for Alloy 22 PCA specimens tested in 1 M NaCl solution 11 with PTFE tape covered ceramic crevice former, but in this case the E R,CREV became stable for a torque higher than 3.4 N·m in 1 M NaCl at 90°C.…”
Section: Crevice Former Materials and Applied Torquesupporting
confidence: 71%
See 1 more Smart Citation
“…They found that when the applied torque is too low, the determined E R,CREV tend to be inordinately high, but for a torque higher than 0.98 N·m (0.1 kgf·m) the measurement becomes stable. The same tendency was displayed for Alloy 22 PCA specimens tested in 1 M NaCl solution 11 with PTFE tape covered ceramic crevice former, but in this case the E R,CREV became stable for a torque higher than 3.4 N·m in 1 M NaCl at 90°C.…”
Section: Crevice Former Materials and Applied Torquesupporting
confidence: 71%
“…or the crossover of the reverse and forward scans (E RCO ) ( Figure 1). Other tests are the Tsujikawa-Hisamatsu Electrochemical (THE) method, for which a round-robin matrix of results is under discussion in ASTM, 11,12 and the potentiostatic (POT) test, which does not have an ASTM standard. 9,13 In the THE method the repassivation potential (E R,CREV ) is the potential at which the anodic current ceases to increase in the potentiostatic decreasing steps (Figure 2).…”
Section: Testing Methodsmentioning
confidence: 99%
“…In recent years, various electrochemical techniques, such as cyclic potentiodynamic polarization [4][5][6][7][8][9], potentiostatic polarization [4][5][6][7], galvanostatic polarization [10], tsujikawa-hisamatsu method [11], electrochemical noise method [12,13] and dynamic electrochemical impedance spectroscopy [14], are being used to asses the crevice corrosion process. The effects of variables, such as crevice former materials, applied torque on crevice formers, chemical elements and crevice geometries on crevice corrosion behavior, have been studied [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of variables, such as crevice former materials, applied torque on crevice formers, chemical elements and crevice geometries on crevice corrosion behavior, have been studied [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation